Tagore’s The home and the world: aesthetics in command - Kumar, Dinesh (Innovative Research Thoughts, 2018)
India is the male dominated society and women are not given equal opportunities to exercise their rights. This phenomenon is seen across the ages and in all the class divisions of the country. No matter which class they belong to, they were bound to be the carriers and representing some ideology that the class or caste believed in. At times, like during freedom struggle, a very few women broke their bounds and entered society to fight for their nation. Many elite classes did not encourage their women to step into that political realm nor wanted them to have knowledge of anything happening out there in the field. Bhadralok is Bengal‟s new class of „gentlefolk‟ and they seem to be arousing in the British India. The class considered that women are not free to step out of their homes to voice out their social and political opinion. But, a very few women did voice out because the nation was in demand for it. The objective of the research is to study the representations of Bimala, the character who represents Bhadralok women and how she is been abused by the lower section for both physical and financial uses through the character, Sandip. The research problematizes the representations of Bimala by Sandip, a man from lower section leads to the abuse of Bimala where she is believed to be someone immoralist and nonconformist, and that is the reason why is been ditched and widowed. The transgression of the Bhadralok woman, where she is represented as Mother of nation and Queen Bee, is merely compensating the original freedom with the intellectual freedom and utilized for the personal needs of people at lower strata.